Community perspectives on substance use among Bhutanese and Iraqi refugees resettled in the United States. Issue 1 (2nd January 2018) - Mirza, Mansha Q.; Harrison, Elizabeth A.; Chang, Hui-Ching; Salo, Corrina D.; Birman, Dina
ABSTRACT: Premigration trauma and postmigration stressors put refugees at high risk for mental health concerns, including substance use. However, there is limited systematic research on substance use in refugee communities exists. We conducted exploratory qualitative research to examine Bhutanese and Iraqi refugee perspectives related to the use of recreational substances after resettlement in the United States. Data were collected through separate focus groups with 28 Bhutanese and 22 Iraqi adult men. Focus groups were facilitated by an experienced clinician with an in-person interpreter, audiorecorded, and transcribed. Transcripts were checked for accurate translation and then analyzed using a conventional content analysis approach. Findings revealed similarities and differences between the two refugee groups with regard to recognizing excessive use, triggers for use, and preferred modes of outreach and intervention. Findings also revealed postmigration changes in substance use behaviors stemming from issues related to access, cost, and perceived legal ramifications.